KOMUNIKASI KEBANGSAAN: MEMAHAMI RELASI KEBANGSAAN DENGAN BENTUK NEGARA KESEJAHTERAAN - Taufik, Cevi M; Darsono, Dono (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
Realizing welfare as the ultimate goal of the state still requires a long struggle. The collective experience of the nation in manifesting welfare has been marked by various events that led to deviations from national ideals. Fundamental disruptions have occurred, each with broad and profound impacts. The emergence of foreign agents seeking to blur and alter the nation’s ideology and aspirations, the formalization of Pancasila, authoritarian leadership that tended to align with the axis of certain states, the rise of oligarchy, and political streams that diverted the nation’s struggle to achieve the ideal of welfare, all became part of these challenges. These events represent episodes in the nation’s journey to uphold Indonesia as an independent, strong, and prosperous nation. Based on these considerations, this study aims to examine the practice of national communication in the effort to achieve a welfare state. The method used in this research is qualitative, emphasizing data analysis drawn from media sources and other documents. The findings show that national communication can serve as an essential aspect in building commitment toward realizing the ideals of a welfare state